Recombinant Chromosome 4 from a Familial Pericentric Inversion: Prenatal and Adulthood Wolf-Hirschhorn Phenotypes - Francesca Malvestiti; Francesco Benedicenti; Simona De Toffol; Sara Chinetti; Adelheid Höller; Beatrice Grimi; Gertrud Fichtel; Monica Braghetto; Cristina Agrati; Eleonora Bonaparte; Federico Maggi; Giuseppe Simoni; et al. (Case Reports in Genetics)
Pericentric inversion of chromosome 4 can give rise to recombinant chromosomes by duplication or deletion of 4p. We report on a familial case of Wolf-Hirschhorn Syndrome characterized by GTG-banding karyotypes, FISH, and array CGH analysis, caused by a recombinant chromosome 4 with terminal 4p16.3 deletion and terminal 4q35.2 duplication. This is an aneusomy due to a recombination which occurred during the meiosis of heterozygote carrier of cryptic pericentric inversion. We also describe the adulthood and prenatal phenotypes associated with the recombinant chromosome 4.